The signal relation diagram – A Metrological Tool?. (October 2018) - Ruhm, Karl H.
Abstract: Relations between signals are important issues in modelling and simulation practice, especially in the field of Metrology. As a formal and descriptive "language", the so-called signal relation diagram (SRD) represents relations between quantity models graphically. It visualises relational structures and generally makes relations more transparent. Signal relation diagrams base on logical and mathematical phrasing. Only a few basic elements are necessary. A straightforward synthesis unites these elements in typical arrangements in a holistic and consistent way. They serve as basic elements and structures in varied fields of Metrology (chemical analysis, environmental investigation, medical imaging, particle observation, flow measurement, surveying), for modelling, description, simulation, error and uncertainty analysis, reconstruction, filtering, verification, and so on. The key task is information, insight, understanding and knowledge.